Enhancing Home and Commercial Security: A Multi-Modal Authentication Framework for Keyless Door Lock Systems - Anand Desai; Chintan Shah; Mandar Bivalkar, (Indian Journal of Cryptography and Network Security (IJCNS), 2025)
The lock-and-key paradigm of yesteryears is vulnerable to the current scenario of more frequent cyber attacks and breaches of physical security, making the current systems ask for more innovative protection for homes and businesses. In this paper, an innovative triadic multimodal authentication framework has been proposed to have facial recognition, voicebased authentication, and number pad entry into the highly elevated security protocol for convenient usage. The current research is well-grounded within a comprehensive review of 50 peer-reviewed studies covering all the critical gaps in today's access control systems, mainly in smart environments where security demands are paramount. The architecture of the proposed system is elaborately delineated in a way that describes the seamless integration of hardware and software components into a robust and adaptable authentication mechanism. Performance evaluations show high accuracy rates in different environmental conditions, and users also give good feedback regarding the ease of use and reliability. This work provides a practical solution to the current security challenges and opens up future research directions by promoting adaptive authentication methodologies and new biometric technologies that can further enhance security in smart environments. The implications of this framework stretch far beyond the individual systems into proposing a template for security improvements in the wider scheme of smart homes and offices as connected systems.